nkx2.1 and nkx2.4 genes function partially redundant during development of the zebrafish hypothalamus, preoptic region, and pallidum - Manoli, Martha; Driever, Wolfgang (Frontiers in Neuroanatomy, 2014)
During ventral forebrain development, orthologs of the homeodomain transcription factor Nkx2.1 control patterning of hypothalamus, preoptic region, and ventral telencephalon. However, the relative contributions of Nkx2.1 and Nkx2.4 to prosencephalon development are poorly understood. Therefore, we analyzed functions of the previously uncharacterized nkx2.4-like zgc:171531 as well as of the presumed nkx2.1 orthologs nkx2.1a and nkx2.1b in zebrafish forebrain development. Our results show that zgc:171531 and nkx2.1a display overlapping expression patterns and a high sequence similarity. Together with a high degree of synteny conservation, these findings indicate that both these genes indeed are paralogs of nkx2.4. As a result, we name zgc:171531 now nkx2.4a, and changed the name of nkx2.1a to nkx2.4b, and of nkx2.1b to nkx2.1. In nkx2.1, nkx2.4a, and nkx2.4b triple morpholino knockdown (nkx2TKD) embryos we observed a loss of the rostral part of prosomere 3 and its derivative posterior tubercular and hypothalamic structures. Furthermore, there was a loss of rostral and intermediate hypothalamus, while a residual preoptic region still develops. The reduction of the ventral diencephalon was accompanied by a ventral expansion of the dorsally expressed pax6, revealing a dorsalization of the basal hypothalamus. Within the telencephalon we observed a loss of pallidal markers, while striatum and pallium are forming. At the neuronal level, nkx2TKD morphants lacked several neurosecretory neuron types, including avp, crh, and pomc expressing cells in the hypothalamus, but still form oxt neurons in the preoptic region. Our data reveals that, while nkx2.1, nkx2.4a, and nkx2.4b genes act partially redundant in hypothalamic development, nkx2.1 is specifically involved in the development of rostral ventral forebrain including the pallidum and preoptic regions, whereas nkx2.4a and nkx2.4b control the intermediate and caudal hypothalamus.